Recycling channel selection and financing strategy for capital-constrained retailers in a two-period, closed-loop supply chain - Zhang, Weisi; Zhang, Tao (Frontiers in Environmental Science, 2022)
This article studies a two-period, closed-loop supply chain (CLSC) with manufacturer or retailer recycling. It establishes a model analysis framework to analyze pricing optimization strategies and the channel-mode selection of electric vehicle batteries and considers manufacturer recycling and retailer recycling scenarios. When a retailer recycles, it needs to invest capital to build its recycling channel and so suffers from capital constraints. For this reason, retailers consider bank loans or trade-credit financing from manufacturers. This work explores a two-stage, CLSC pricing strategy that considers consumers’ preferences for remanufactured products and recycling rates, and it investigates financing channels for capital-constrained retailers. It analyzes optimal equilibrium strategies in three modes and compares the recycling and financing modes. Through numerical examples, it analyzes the effects of value preference rates and recycling rates of remanufactured products on supply chain profits, product demand, and model selection. The results show that the recycling rate can effectively incentivize the demand for new products in the first period. For any remanufactured product recycling cost, the manufacturer’s profit is most significant in the retailer-recycling bank financing model, and the retailer’s profit is largest in the manufacturer recycling model. As the consumer preference rate for remanufactured products increases, the demand for new products in the second stage decreases and the demand for remanufactured products increases. The retailer recycling trade-credit financing from the manufacturer model gives the largest profit to the retailer when the preference rate is significant or when the preference rate is low with a moderate recycling rate.